CPS302 - Data Communication and Networking August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Unlversiti Sains Malaysia) August/September 1998 CPS302 - Data Communication and Networking Time : [3 hours] INSTRUCTIONS TO CANDIDATES: Please ensure that this examination paper contains EIGHT questions in FOUR printed pages before you start the examination. Answer ALL questions only. On each page, write only your Student ID.